Bridging Research and Public Health: Reflections on the Vol. 5, Issue 8, 2023 - Amgain, Kapil (Europasian Journal of Medical Sciences, 2025)
The editorial board of Europasian Journal of Medical Sciences (EJMS) is happy to wrap-up the continuous Issue 8, Volume 5 on 30 December 2023. This issue presents an eclectic array of articles that not only address critical health challenges in Nepal but also offer insights with broader global implications. The collected works, spanning original research, review articles, and brief communications, underscore the dynamic interplay between clinical innovation, public health policy, and community well-being. The articles featured herein reflect a multidisciplinary approach, addressing both immediate clinical challenges and broader public health imperatives. Collectively, the studies highlight the importance of context-specific research and underscore the need for integrated healthcare strategies that resonate both locally and globally. This editorial aims to capture the essence of the current issue and to stimulate ongoing dialogue among researchers and practitioners. The contributions featured herein are a testament to the vibrant research culture in Nepal and a reminder of the transformative power of evidence-based practice in advancing public health.